GEOMYTHOLOGICAL APPROACH OF ASOPOS RIVER (AEGINA, GREECE) - Mariolakos, I.; Theocharis, D. (Bulletin of the Geological Society of Greece, 2010)
In Greek Mythology rivers are, with some exceptions, Gods and they were “born” by the Titans, Oceanus and Tethys. The River Gods are also considered to have given birth to some Islands. Amongst them Asopos River has the most important position as he is considered to have given birth to Aegina, Salamis, Euboea and some other islands as well. The myth of Asopos River is remarkable because it is a typical case where the physical-geological evolution allows us to explain the myth, and at the same time, the myth lets us to give an explanation about the diachronic route of Asopos riverbed, especially during the crucial period between 18,000 to 6,000 BP. The area, known as Saronic Gulf today, used to partly be land, including a great lake, the Epidaurus Paleolake, until 13,000 BP. Asopos River, nowadays known as “Rema tis Skotinis”, is located on Aegina island. In this paper we are trying to investigate whether Asopos River was flowing either into the Epidaurus Paleolake or into the Saronic Paleogulf.